The ability of the fungus Glomus sp and some species of Trichoderma spp in suppression Macrophmina phaseolina pathogenic fungus that causes charcoal rot disease of sunflower - L. Alwan, Sabah; A Matlood, Abdulnabi (Al-Qadisiyah Journal of Pure Science, 2018)
The study used Glomus sp and some species of Trichoderma spp in Resistance - disease of charcoal rot of sunflower plant that caused by Macrophmina phaseolina where it found that the types of Trichoderma spp have inhibition a role to Macrophmina phaseolina where all isolates of Trichoderma spp have a good ability towards the pathogenic M. phaseolina in spoting inhabitation method where the inhibition zone was 2.6 , 2.5, 2.4 , 2.4 and 2.4 cm for T.h, T. r , T. t , T.a and T.v , respectively, as well as the double inhabitation method the T.harizanum was significantly the best comparative with the rest of the types of Trichoderma spp. the study, the GCMS device was identified many chemical compounds of Trichoderma harizanum that act as anti- biotic such as Linoleic acid It was found that Glomus sp have ability to motivate resistance in sunflower plant against pathogenic fungus M . phaseolina through deposition lignin on the walls of plant cells when used types of bioagent Trichoderma spp . outweigh all kinds of fungus Trichoderma spp used may have reduced the severity of infection by the fungus M.phaseolina when used in contaminated soil fungus pathogen three days but the fungus Glomus sp and T.h and T.v were the most influential and significant difference from other rest of fungi.